THE QUALITY OF APPLES AND WINE MATERIALS DEPENDS ON THE TECHNOLOGY OF CULTIVATION - Литовченко, Александр; Войцеховский, Владимир; Мазур, Борис; Петренко, Мирослава; Луцкова, Виктория; Мулярчук, Оксана; Гринчак, Наталья; Кузнецов, Андрей; Старенец, Екатерина (SWorldJournal, 2021)
The results of researches of influence of technology of cultivation of perspective grades on quality of fruits are resulted. The influence of wine yeast on the quality of natural varietal apple wine materials is revealed. The highest quality fruits and th